Comparison of Class A pan, tank, and Piche evaporimeter (MAUSAM, 1980)
The object of this paper is to study the variation of evaporation Karaj (Long. 51 deg. 00 min. E,  Lat. 35 deg. 48 min., Alt. 1321 m) by different evaporimeters and comparison, the results to find out suitable conversion factor. The results of analysis of 2 years (1975-76) data of evaporation show that the correlation Coefficient between Piche and U.S A. evaporimeter, is higher than that U.S.A. and U.S.S.R, evaporimeters. Conversion factors varied from month to month.